Network Digital Twin Toward Networking, Telecommunications, and Traffic Engineering: A Survey - Reza Poorzare; Dimitris N. Kanellopoulos; Varun Kumar Sharma; Poulami Dalapati; Oliver P. Waldhorst (IEEE Access)
Network Digital Twin (NDT) is an evolving technology that provides a framework through which a network administrator can have a virtual representation of a computer network. As a result, analysis, monitoring, testing, running new protocols, and more can be performed using the NDT before the final deployment of the developed approach. In this way, the consequences of direct deployment and the negative impact on network operations can be avoided. Telecommunications, along with traffic engineering as one of its critical components, play a prominent role across various networking domains, including Internet service providers, data centers, cellular networks, intelligent transportation systems, and smart cities. In this context, NDT has the potential to serve as a key enabler for optimizing these domains by providing a digital framework, which can facilitate the evaluation and enhancement of different scenarios. Accordingly, this paper presents a comprehensive survey on how NDT can facilitate advancements in network traffic engineering across a wide range of networking domains. First, we start with an in-depth analysis of the evolution of the network digital twin technology and provide a comparison with simulation tools. Next, we examine the role of NDT in various networking and telecommunication domains. We also explore the applicability of NDT technology from a traffic engineering perspective across different network types. Subsequently, we highlight key open research questions and potential future directions that warrant further investigation. Finally, we conclude by outlining the promising future trajectory of NDT within the aforementioned domains.